Researching From Buried Experiences: Collaborative Inquiry With Asian American Youth (LEARNing Landscapes, 2015)
This article reports on an out-of-school practitioner researcher study, the Community Researchers Project, involving predominately Indonesian youth who were members of a Catholic parish in a diverse multilingual neighborhood of our city. The lives and learning of many of the youth in the Indonesian immigrant community were, to a large extent, invisible in the research literature or homogenized through broader generalizations regarding Asian Americans, such as the myth of the "model minority." Through analysis of several representative student inquiries, we argue that practitioner research can be an effective methodological vehicle for unearthing "buried" personal and collective histories that impact students.
Keywords: practitioner research; youth; colective history